Relationship Between Post-traumatic Stress Symptoms and Anticipatory Grief in Family Caregivers of Patients With Advanced Lung Cancer: The Mediation Role of Illness Uncertainty - Sun, Di; Mao, Zhihui; Zhang, Xu; Li, Jiaojiao; Zhang, Lijuan (Frontiers in Psychiatry, 2022)
Objective To explore the interrelationship between post-traumatic stress symptoms (PTSS), illness uncertainty (IU), and anticipatory grief (AG). Methods Structural equation modeling with bootstrapping estimation was conducted using data from a convenience sample of 254 family caregivers of patients with advanced lung cancer in China. Participants were recruited from a public cancer hospital in Shenyang, China. The family caregivers completed the Impact of Events Scale-Revised, Uncertainty in Illness Scale Family Caregiver Version, and Anticipatory Grief Scale. Results The measurement model has good reliability and validity, and the final model fit the data well. PTSS positively influenced AG (direct effect estimate = 0.391, p = 0.002). Moreover, IU was found to mediate the relationship between PTSS and AG (Indirect effects estimate = 0.168, p = 0.005). The mediating effect of IU accounted for up to 30.1% of the total effect. Conclusion IU mediated the relationship between PTSS and AG. Healthcare professionals should continuously assess PTSS, IU and AG levels in FCs and provide effective intervention options for mitigation.